Donor miR‐196a‐2 polymorphism is associated with hepatocellular carcinoma recurrence after liver transplantation in a Han Chinese population. Issue 3 (14th September 2015) - Xu, Xiao; Ling, Qi; Wang, Jianguo; Xie, Haiyang; Wei, Xuyong; Lu, Di; Hu, Qichao; Zhang, Xuanyu; Wu, Liming; Zhou, Lin; Zheng, Shusen
Abstract : Recurrence of hepatocellular carcinoma (HCC) is one of the leading causes of death after liver transplantation (LT). We aim to evaluate the association of donor and recipient single nucleotide polymorphisms (SNPs) with the risk of HCC recurrence after LT. A total of 155 adult patients who underwent primary LT for HCC were enrolled. Ten SNPs associated with HCC susceptibility were genotyped. Patients who received donor livers with the rs11614913 homozygous CC variant presented significantly higher recurrence rates of HCC (41.7 vs . 15.3%, p = 0.009) and lower cumulative tumor‐free survival ( p = 0.005) than those who received TT wild‐type donor livers. The donor rs11614913 genetic variant was an independent risk factor for HCC recurrence (odds ratio = 2 per each C allele, p < 0.05) and could significantly improve the predictive abilities of clinical models (Milan, UCSF and Hangzhou criteria). Donor livers homozygous for rs11614913 CC were associated with a higher miR‐196a expression than TT ( p = 0.002). In a lentiviral infection of mouse liver and orthotopic mouse model of HCC, the liver miR‐196a overexpression group showed a significantly larger tumor size than the control group ( p = 0.001). There is a close association between the tumor size and expression of miR‐196a in the liver ( r = 0.693, p = 0.001). In conclusion, the donor miR‐196a‐2 rs11614913 polymorphism is associated with HCC recurrence after LT and improves the predictive value of clinical models. The overexpression of miR‐196a in the liver might provide a tumor‐favorable environment for the development of HCC. Abstract : What's new? Liver transplantation produces a favorable outcome for many patients with early‐stage, unresectable hepatocellular carcinoma (HCC). However, its impact on survival rates could be greater, if the mechanisms driving HCC recurrence after transplantation were known. Here, HCC recurrence following liver transplantation was linked to the presence of a polymorphism in donor livers. The variant, rs11614913, was associated with increased expression of microRNA‐196a. In an orthotopic HCC mouse model, mi‐196a overexpression resulted in a significant increase in liver tumor size. The combined use of patient selection criteria and donor liver genotype could refine clinical prediction models.